An argument against using standardized test scores for placement of international undergraduate students in English as a Second Language (ESL) courses. (October 2013) - Kokhan, Kateryna
Development and administration of institutional ESL placement tests require a great deal of financial and human resources. Due to a steady increase in the number of international students studying in the United States, some US universities have started to consider using standardized test scores for ESL placement. The English Placement Test (EPT) is a locally administered ESL placement test at the University of Illinois at Urbana-Champaign (UIUC). This study examines the appropriateness of using pre-arrival SAT, ACT, and TOEFL iBT test scores as an alternative to the EPT for placement of international undergraduate students into one of the two levels of ESL writing courses at UIUC. Exploratory analysis shows that only the lowest SAT Reading and ACT English scores, and the highest TOEFL iBT total and Writing section scores can separate the students between the two placement courses. However, the number of undergraduate ESL students, who scored at the lowest and highest ends of each of these test scales, has been very low over the last six years (less than 5%). Thus, setting cutoff scores for such a small fraction of the ESL population may not be very practical. As far as the majority of the undergraduate ESL population is concerned, there is about a 40% chance that they may be misplaced if the placement decision is made solely on the standardized test scores.